Report of the trustees of the Lurgan Loan Fund to the Commissioners of the Loan Fund Board of Ireland - Hancock, John (Statistical and Social Inquiry Society of Ireland, 1849)
We, the Trustees of the Lurgan Loan Fund, beg to report to the Commissioners of the Loan Fund Board of Ireland, that after nearly ten years' experience in this district, and after the most careful inquiries, we have arrived at the conclusion that the charitable loan fund system is productive of more evil than good, and we have come to the determination of closing the Lurgan Loan Fund as soon as practicable.
Read March 20th 1848
Keywords: Loan fund; Money lending; 314.15